Multi-Stakeholder Partnership Strategy of SMK N 1 Dukuhturi With Industry and the World of Work - Wibowo, Aris Setyo; Mahmud, Amir; Kusmuriyanto, Kusmuriyanto (Universitas Negeri Semarang, 2024)
The absorption of SMK N 1 Dukuhturi graduates by industry and the world of work is inversely proportional to the absorption of vocational school/SMK graduates in Tegal Regency. This research aims to analyze the implementation of the Multi-Stakeholder Partnership Strategy at SMK N 1 Dukuhturi with Industry and the World of Work. The research uses a qualitative phenomenological approach. The data collection is carried out through interviews with the Vice Principal for Public Relations, BK (Guidance and Counseling) Teacher Coordinator, Head of BKK, KKK, Head of PR of Swalayan KITA, and Head of PSDKU BSI. The data analysis technique used in this research is the Domain Analysis Technique of the Miles and Huberman model. The research reveals the stages of implementing the Multi-Stakeholder Partnership Strategy of SMK N 1 Dukuhturi with Industry and the World of Work, consisting of Initiating, Adaptive Learning, Collaborative Action, and Reflective Monitoring. Based on the research results, it is found that the implementation of collaboration does not always foster professional empathy which can be optimized to overcome collaboration obstacles. To increase the effectiveness of the Multi Stakeholder Partnership Strategy, it is recommended that the government intervene to ensure collaborative leadership between parties involved in the collaboration.